Small bowel enterocutaneous fistulae: is waiting worth? - Kumar, Mukesh; Jauhari, Abhinav (International Journal of Research in Medical Sciences, 2017)
Background: Enterocutaneous fistula represents a group of complex intraperitoneal infectious processes. Even with recent advances in Para surgical management, critical care and nutritional support, enterocutaneous fistulas remain great challenges to the general surgeon. Mortality remains high largely due to frequent complications of sepsis and malnutrition. Most enterocutaneous fistulas occur following emergency abdominal surgeries and only 15-25% of spontaneous enterocutaneous fistulas are the result of underlying diseases such as Crohn’s diseases, radiation enteritis or diverticular disease. Expectant treatment consisting of octreotide, TPN, and antibiotics waiting for spontaneous closure is associated with high costs, high mortality and prolonged morbidity. In our country, there is need to abandon expectant lines of management for a more aggressive surgical approach once the fluid and electrolyte disturbance and sepsis have been corrected. Methods: The aim of the present study was to audit the result of an aggressive approach in patients with enterocutaneous fistulas and to identify the time of convalescence prior to restorative surgery thereby reducing the morbidity and mortality associated with them. The focus of this study was to determine whether, in patients with fistulae, early intervention resulted in low mortality and morbidity. Results: In the present study, 64 cases of small bowel enterocutaneous fistulas were taken, which were either operated in Patna medical college and hospital or outside in year 2011-13. Majority of patients were <60 years of age. Out of the total population (n=64), 50 patients were <60 years and 14 patients were ≥60 years, with mean age of 46 years (range 17-75 years). The percentage of male population was 56.2 and that of female was 43.8. Mortality was also higher in patients with sepsis, age>60 years and in patients with preoperative albumin below 3.0g/dl (p value>0.05). Early surgical intervention resulted in good patient outcomes as compared to conservative treatment (p value-0.0418). Mortality was higher in patients with foregut fistulae (p value-0.0178) and high output fistulae (p value-0.0309). Conclusions: This study shows that early surgery can result in good patient outcomes. Initial emphasis should be on the treatment of septic foci, aim to improve to patient’s condition. Rather than following a prolonged conservative line of management, surgical repair should be performed when the patient is stable.